2017
DOI: 10.1142/s0218495817500066
|View full text |Cite
|
Sign up to set email alerts
|

Role Models and Entrepreneurial Intention: The Moderating Effects of Experience, Locus of Control and Self-Esteem

Abstract: International audienceThis article demonstrates that the impact of role models (RMs) on students’ self-efficacy and entrepreneurial intention is moderated by their entrepreneurial experience and personality variables such as self-esteem and locus of control. 276 students enrolled in an entrepreneurship education programs (EEPs) were exposed to either a positive or a negative sensitisation message by alumni who became entrepreneurs to test its impact on the students’ self-efficacy and entrepreneurial intention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 82 publications
3
36
0
5
Order By: Relevance
“…In other words, individuals with successful role models enjoy a greater amount of self-efficacy (Boyd and Vozikis 1994) and have lower fear of failure (Wyrwich et al 2018) due to their role models. Gibson (2004) and Buunk and Gibson (2007) found that making 'upward or downward comparisons' with different types of role models has positive effects on entrepreneurial intentions (Brunel et al 2017). In line with social comparison theory, they find that individuals usually make an 'upward comparison' with the model and believe they will be at least as successful as the model they observed.…”
Section: Successful Versus Unsuccessful Models (7 Papers)mentioning
confidence: 80%
See 3 more Smart Citations
“…In other words, individuals with successful role models enjoy a greater amount of self-efficacy (Boyd and Vozikis 1994) and have lower fear of failure (Wyrwich et al 2018) due to their role models. Gibson (2004) and Buunk and Gibson (2007) found that making 'upward or downward comparisons' with different types of role models has positive effects on entrepreneurial intentions (Brunel et al 2017). In line with social comparison theory, they find that individuals usually make an 'upward comparison' with the model and believe they will be at least as successful as the model they observed.…”
Section: Successful Versus Unsuccessful Models (7 Papers)mentioning
confidence: 80%
“…Consequently, it is argued that not only the existence of role models is consequential but also the achievements of an entrepreneurial career conveyed by those role models (Davidsson 1995;Scherer et al 1989a). For example, several findings emphasize that exposure to a successful ERM has a favorable impact on entrepreneurial behavior (e.g., Boissin et al 2011;Boyd and Vozikis 1994;Brunel et al 2017). This exposure has been argued to increase entrepreneurial intentions to start new businesses by facilitating information concerning attainable opportunities, by providing particular guidance and help, or by creating encouraging surroundings that foster entrepreneurial outcomes (BarNir et al 2011).…”
Section: Literature With a Focus On The Types Of Role Models (By Whommentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the findings also show that internal locus of control is critical to building individual intention in entrepreneurship [17]. Personality traits such as locus of control play a decisive role in increasing entrepreneurial intention, as individuals with an internal locus of control believe that they will succeed in entrepreneurship [18]. Internal locus of control is the individual's perception that an event depends on the behavior or the characteristics inherent in the individual [19].…”
Section: Introductionmentioning
confidence: 83%